Analysis on the Next Generation Assault Rifles and Ammunition Designed for the US Army - Miroslav DIMITROV (Wojskowa Akademia Techniczna, 2021)
In recent years, the US Army began actively looking for a replacement for the 5.56 mm M16/M4 assault rifle, which currently is the standard issue weapon for the infantry. The US Army has selected three potential companies to produce the next generation assault weapon. These are the following companies Sig Sauer, General Dynamics, and Textron systems. All companies have submitted prototypes for the next generation assault rifle that are the subject of the analysis in this paper. In addition, the companies also offer new types of ammunition for the abovementioned systems. The purpose of this paper is to compare the three assault rifle prototypes and the ammunition they use to highlight their potential strengths and weaknesses and to address possible reliability problems. Although many of the specifications of the weapons are the subject to company secret, the paper will provide a comparative analysis of small arms samples that plan to replace the 5.56 mm M16/M4 assault rifle, according to available information from various sources.
Keywords: Konstrukcja broni strzeleckiej i amunicji